Evaluation of Rosmarinus officinalis Leaves Essential Oils Activity Against Vancomycin Intermediate Staphylococcus aureus (VISA) Isolated from Baghdad Hospital Patients - Al-Hayali, Osamah Z.; AL Marjani, Mohamed. F.; Maleki , Abbas (Iraqi Journal of Science, 2023)
Rosemary is a well-known aromatic and medicinal plant used to treat various ailments. This study evaluated Rosmarinus officinalis essential oil for its phytochemical and antibacterial properties. The essential oil was analysed by using a gas chromatography-mass Spectrometry (GC-MS) that revealed the common chemicals containing verbenone 36.20% and 1,8-cineol (Eucalyptol) 12.14%. Extracted essential oils were tested for antibacterial activity against vancomycin intermediate Staphylococcus aureus (VISA), a strain of bacteria obtained locally from bacteremia patients. Three isolates were found to be VISA positive using the E-test (strips) and the population analysis profile method (PAP). VISA showed lower resistance to the essential oils (MIC: Minimum inhibitory concentration, MIC = 1.5 mg/ml). Overall, the genetic influence of VISA was evaluated by looking at the hld gene expression after being isolated from blood samples and RNA extraction for qRT-PCR to determine hld gene expression. R. officinalis gene expression was analysed and calculated by using real-time PCR of RNA which revealed that it had decreased.